Impact of Clot Shape on Successful M1 Endovascular Reperfusion - Guenego, Adrien; Fahed, Robert; Sussman, Eric S.; Leipzig, Matthew; Albers, Gregory W.; Martin, Blake W.; Marcellus, David G.; Kuraitis, Gabriella; Marks, Michael P.; Lansberg, Maarten G.; Wintermark, Max; Heit, Jeremy J. (Frontiers in Neurology, 2021)
Objectives: The susceptibility-vessel-sign (SVS) allows thrombus visualization, length estimation and composition, and it may impact reperfusion during mechanical thrombectomy (MT). SVS can also describe thrombus shape in the occluded artery: in the straight M1-segment (S-shaped), or in an angulated/traversing a bifurcation segment (A-shaped). We determined whether SVS clot shape influenced reperfusion and outcomes after MT for proximal middle-cerebral-artery (M1) occlusions. Methods: Between May 2015 and March 2018, consecutive patients who underwent MT at one comprehensive stroke center and who had a baseline MRI with a T2* sequence were included. Clinical, procedural and radiographic data, including clot shape on SVS (angulated/bifurcation [A-SVS] versus straight [S-SVS]) and length were assessed. Primary outcome was successful reperfusion (TICI 2b-3). Secondary outcome were MT complication rates, MT reperfusion time, and clinical outcome at 90-days. Predictors of outcome were assessed with univariate and multivariate analyses. Results: A total of 62 patients were included. 56% (35/62) had an A-SVS. Clots were significantly longer in the A-SVS group (19mm versus 8mm p=0.0002). Groups were otherwise well matched with regard to baseline characteristics. There was a significantly lower rate of successful reperfusion in the A-SVS cohort (83%) compared to the S-SVS cohort (96%) in multivariable analysis (OR 0.04 [95% CI, 0.002-0.58], p=0.02). There was no significant difference in long term clinical outcome between groups. Conclusion: Clot shape as determined on T2* imaging, in patients presenting with M1 occlusion appears to be a predictor of successful reperfusion after MT. Angulated and bifurcating clots are associated with poorer rates of successful reperfusion.